Enhancing MaaS user satisfaction through strategic marketing: The synergy of sustainability and service experience - LiYan Bu; Hong Chen; WeiCheng Pan; HeSen Li (PLoS ONE, 2025)
As urbanization intensifies and the need for sustainable transportation grows, Mobility as a Service (MaaS) emerges as a promising solution to urban mobility challenges. This study seeks to explore the underlying mechanisms of MaaS from a sustainability perspective and to assess its impact on service experience and user satisfaction. Additionally, it examines how user satisfaction influences the broader adoption of MaaS. To address these objectives, relevant hypotheses were posited, and hypothetical models were constructed based on a comprehensive review of the literature. The interconnections among sustainability, service experience, and user satisfaction within MaaS were rigorously analyzed employing both a survey methodology and structural equation modeling for data analysis. The findings support five hypotheses, affirming that sustainability significantly influences the MaaS service experience, which in turn impacts user satisfaction. Furthermore, sustainability directly contributes to user satisfaction and is crucial for its enhancement. User satisfaction also positively affects the dissemination of MaaS services. Notably, the study identifies a critical mediating role of service experience in the utilization of MaaS, linking sustainability and user satisfaction. This research offers both theoretical insights and practical guidance for understanding the operational dynamics of MaaS and improving the user experience.